Molecular detection of marine nematodes from environmental samples: overcoming eukaryotic interference - Bhadury, P; Austen, M; Bilton, D; Lambshead, P; Rogers, A; Smerdon, G (2006)
Nematodes form an important and dominant component of many benthic marine ecosystems, but are frequently neglected by marine ecologists because of the time-consuming nature of their identification. Molecular techniques provide powerful tools for the rapid assessment of biodiversity, although few attempts have been made to apply these to marine meiofauna. We evaluated the success of 2 primer sets in amplifying nematode 18S rRNA from DNA templates extracted directly from marine and estuarine sediments. PCR products were separated using denaturing gradient gel electrophoresis (DGGE), and some of the intense DGGE bands were excised, cloned and sequenced to confirm their nematode origin. Initially, other eukaryotic 18S rRNA regions co-amplified with those from nematodes, possibly as a result of the high relative abundance and biomass of other organisms in the studied sediments. These problems were overcome by designing and evaluating consensus primers that selectively amplified nematode ribosomal regions from environmental DNA. Approximately 10 to 12 taxa from each site were detected in the denaturing gel in this study. Tentative affiliations of some the DGGE bands re-amplified using nematode-specific primers were determined by comparing with known marine nematode 18S rRNA sequences in a phylogenetic tree. Our study demonstrates for the first time that PCR combined with DGGE can be used to explore the community composition of many meiofaunal groups, such as nematodes, from DNA extracted directly from environmental samples. © Inter-Research 2006.